2018
DOI: 10.1002/jlcr.3631
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of microtubule‐targeted theranostic methyl N‐[5‐(3’‐radiohalobenzoyl)‐1H‐benzimidazol‐2‐yl]carbamates

Abstract: Microtubules are a target for a broad spectrum of drugs used as chemotherapeutics to treat hematological malignancies and solid tumors. Most of these drugs have significant dose-limiting toxicities including peripheral neuropathies that can be debilitating and permanent. In an ongoing effort to develop safer and more effective drugs, benzimidazole-based compounds are being developed as replacement for vincristine and similar agents. In this report, we describe radiosyntheses of novel microtubule-targeting meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The processes shown in Schemes and involve three consecutive steps: the initial preparation of nonradioactive iodo analogs followed by the stannylation of iodides to the corresponding stannanes and the subsequent non-carrier-added electrophilic 125 I-iododestannylation of organotin precursors to the target 125 I-iodinated products. This well-proven radioiodination sequence based on the modified Stille coupling and originally applied in our laboratories to produce no-carrier-added 5-[ 125 I]­iodo-2′-deoxyuridine and other radiolabeled compounds served just as effectively in this project.…”
Section: Resultsmentioning
confidence: 99%
“…The processes shown in Schemes and involve three consecutive steps: the initial preparation of nonradioactive iodo analogs followed by the stannylation of iodides to the corresponding stannanes and the subsequent non-carrier-added electrophilic 125 I-iododestannylation of organotin precursors to the target 125 I-iodinated products. This well-proven radioiodination sequence based on the modified Stille coupling and originally applied in our laboratories to produce no-carrier-added 5-[ 125 I]­iodo-2′-deoxyuridine and other radiolabeled compounds served just as effectively in this project.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical structures of compounds evaluated in this study are shown in Figure 1 and they were synthesized as described previously. 22 Mebendazole 3 was purchased from Sigma-Aldrich. Physicochemical parameters of evaluated compounds are listed in Supplementary Table S1.…”
Section: Buffers and Chemicalsmentioning
confidence: 99%
“…Chemical structures of compounds evaluated in this study are shown in Figure 1. Methyl N-[5-(3 0 -radiohalobenzoyl)-1H-benzimidazol-2-yl] carbamates 1 and 2 were synthesized as previously described (Kortylewicz & Baranowska-Kortylewicz, 2018). All agents used in the biological evaluation studies were purified on an HPLC system.…”
Section: Synthesis and Purification Of Compounds Evaluated In This mentioning
confidence: 99%
“…When radiolabeled with αor β-particle emitting radiohalides, these new BCars can be developed into an effective and safe treatment modality across a wide spectrum of cancers. They can function as theranostics, that is, can be also radiolabeled without reshaping their chemical structure with either PET-and SPECT-compatible radionuclides for imaging (Kortylewicz & Baranowska-Kortylewicz, 2018). To date, only a few attempts have been made to develop microtubule-targeted imaging agents, which can measure the drug concentration in tumors and facilitate rational treatment choices (Korde et al, 2006;van der Veldt et al, 2010;van der Veldt et al, 2011;Zareneyrizi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%